Persepsi Santri Terhadap Kegiatan English Club dalam Meningkatkan Motivasi Untuk Berbicara Bahasa Inggris - Fitri Ayu; Hanifah, Ghina; Zulhermindra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
In order to prevent other languages, such English, from receiving less attention or from developing as much for pupils at Islamic boarding schools, they are typically required to utilize Arabic in daily communication. The purpose of this study is to boost students' desire to use English through English Club activities. At the Thawalib Gunung Padang Panjang Modern Islamic Boarding School, Joint Field Practice or PLB students from the English Language Education Study Program at UIN Mahmud Yunus Batusangkar conducted this English Club activity. Three steps make up this English Club activity: the first stage involves supplying the necessary materials; the second stage involves practice and student performance; and the third stage involves evaluating the activity by speaking with students who have participated in English Club activities. The interviews revealed that many students were encouraged to speak English by English club activities, that some terms were challenging to read, and that English was not used frequently enough in daily life while they were attending the Islamic boarding school. Based on the results found in this research shows how important English Club activities are if carried out in Islamic boarding schools because apart from being able to speak Arabic, students can also master English.